Soluble and transparent polyimides with high Tgs from a new semi-aliphatic diamine with cyclohexyl and ortho-methyl groups. (June 2021) - He, Xiaoqian; Wang, Shoubai; Wu, Xiuming; Shu, Chen; Fan, Xiang; Yu, Zhenhai; Huang, Wei
Herein a semi-aliphatic diamine 4, 4′-(cyclohexylmethylene)bis(2-methylaniline) (CHMBMA) with a pendant cyclohexyl and two ortho-substituted methyl groups is synthesized from o-toluidine and cyclohexanecarbaldehyde by Mannich and rearrangement reactions. Then CHMBMA is polycondensed with five commercial aromatic dianhydrides by the high-temperature one-step method with the thermal imidization to produce a series of polyimides (PIs, PI-H(1–5)). The weight-averaged molecular weights ( M w s) of PI-H(1–5) are in the range from 9.08 × 10 4 to 27.48 × 10 4 g mol −1 with the polydispersity indices (PDI) from 3.29 to 6.13 by gel permeation chromatography (GPC) measurement. They are soluble in common organic solvents (such as THF, CHCl3 etc.) and can form transparent, tough films with light-color (Thickness: 20–26 μm) by the solution-casting method. The light transmittance of them is above 80% in the visible range from 400 to 760 nm. They exhibit excellent mechanical properties with tensile strength from 72.2 to 97.06 MPa and tensile modulus from 0.9 to 1.9 GPa. Furthermore, they also display low water absorption rates (<2.5%), good thermal stability (5% weight loss temperatures ( T 5% ) in the range from 466 to 480°C under N2 atmosphere and high glass transition temperatures ( T g s ≥ 319°C). As comparison, we also synthesize these PIs (PI-L(1–5)) by the low-temperature two-step method with the chemical imidization. The M w s of PI-L(1–5) are lower than those of PI-H(1–5), but the film color of PI-L(1–5) is relatively lighter than the corresponding one of PI-H(1–5). In summary, the introduction of cyclohexyl and ortho-substituted methyl groups into the backbone can improve the solubility of PIs and the transparency of their corresponding films without reducing their T g s.